How dark is my flower Yosano Akiko and the invention of romantic love - Morton, Leith 1951- (University of Michigan Press, 2023)
The poetry of Yosano Akiko covers all the many and varied aspects of the experience of love--from early romantic encounters between the lover and beloved to the intimate pleasures of mutual infatuation and then true love. The journey outlined in Akiko's verse also grapples with jealousy and unrequited passion, as Akiko's poem-narrative treats the rivalry between herself and her best friend, the poet Yamakawa Tomiko, for the affection of the dashing young literary lion, Yosano Tekkan, who later became Akiko's husband. Thus, How Dark Is My Flower: Yosano Akiko and the Invention of Romantic Love tells a number of stories: a real-life romance unfolds in the poetry of these three poets examined in the book, as well as the story of the journey from romanticism to modernism undertaken by early 20th century Japanese poetry. How Dark Is My Flower emphasizes the astonishing innovations in diction and style, not to mention content, in Akiko's work that transformed the tanka genre from a hidebound and conservative mode of verse to something much more daring and modern. This book pays particular attention to poetry, particularly the tanka genre, in the evolution of modernism in Japanese literature and breaks new ground in the study of modern Japanese literature by examining the invention and evolution of the concept of romantic love
Keywords: Yosano, Akiko -- 1878-1942; Tanka -- Literatur; Liebesdichtung; Yosano, Akiko / 1878-1942 / History and criticism; Love / Japan / 20th century / Poetry; Waka / Women authors / 20th century; Modernism (Literature) / Japan / History / 20th century; Women poets, Japanese / 20th century / Biography; Yosano, Tekkan / 1873-1935 / Friends and associates; Yamakawa, Tomiko / 1879-1909 / Friends and associates; Yamakawa, Tomiko / 1879-1909; Yosano, Akiko / 1878-1942; Yosano, Tekkan / 1873-1935; Friendship; Love; Modernism (Literature); Waka / Women authors; Women poets, Japanese; Japan; 1900-1999; Biographies; Criticism, interpretation, etc; History; Poetry